Influence of the Guided Inquiry Learning Model Assisted by a Two-stay Two Stray towards Chemistry Learning Outcomes of High School Students - Dahlia Sofiyatun; Minarni R. Jura; Sri M. Sabang (Jurnal Akademika Kimia, 2021)
This study aimed to determine the influence of the guided inquiry learning model assisted by two stay two stray toward learning outcomes of students on chemistry at SMA 7 Palu. The type of study was Pre-experimental with a one-shot case study design. The sample was prepared using the purposive sampling technique with a sample consisting of Class XI Science 4 as the experimental class 1, and Class XI Science 2 as the experimental class 2. Both classes consisted of 28 students. The research instruments were the learning outcomes tests, student worksheets, and observation sheets that have been validated theoretically and empirically. Data of learning outcomes was analyzed using inferential statistical analysis with a prerequisite test: normality, homogeneity, and t-test hypothesis test (right side). The results showed that the average learning outcomes for experimental class 1 was 62.32, and for experimental class 2 was 50.29, with standard deviations of 12.58 and 12.05, respectively. Hypothesis test obtained tcount>ttable or 4.04 > 1.67, so H1 is accepted. The average learning outcomes of students in the experimental class 1 with guided inquiry learning model assisted by two stay two stray is higher than in the experimental class 2 with a guided inquiry learning model. Guided inquiry learning model assisted by two stay two stray influences learning outcomes of students at SMA 7 Palu.